2012
DOI: 10.4319/lo.2012.57.1.0211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changes in temperature and food on the development of Calanus finmarchicus and Calanus helgolandicus populations

Abstract: We studied the response in development times of Calanus finmarchicus and Calanus helgolandicus to changes in temperature and food conditions. Grazing experiments were performed at different temperatures for both species, and the results were implemented in a stage-resolved zooplankton population model that predicted development times from biomass increments controlled by ingestion and metabolic losses. Predictions were validated against development data from the literature, and show that C. finmarchicus develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 45 publications
(81 reference statements)
2
47
0
Order By: Relevance
“…to be suppressed at low temperatures, i.e., to show a very high Q 10 compared with the community-level value (Campbell et al, 2001;Møller et al, 2012).…”
Section: Global Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…to be suppressed at low temperatures, i.e., to show a very high Q 10 compared with the community-level value (Campbell et al, 2001;Møller et al, 2012).…”
Section: Global Behaviormentioning
confidence: 99%
“…It is not always fair, however, to associate a particular u 0 value with a particular species over the full range of temperatures included. As discuss further, the temperature response of an individual species is often dome-shaped, a window of habitat tolerance (Møller et al, 2012;Alcaraz et al, 2014), whereas Coltrane 1.0 uses the monotonic, power-law response observable at the community level (Forster et al, 2011). C. finmarchicus, for example, is fit well by u 0 = 0.007 d −1 at higher temperatures (4-12 • C), whereas near 0 • C in Disko Bay, it has been observed to be considerably smaller than extrapolation along the u 0 = 0.007 d −1 power law would predict.…”
Section: Global Behaviormentioning
confidence: 99%
“…Based on our results, changes in salinity and stratification due to meltwater 8 / ARCTIC, ANTARCTIC, AND ALPINE RESEARCH runoff would strongly influence the free-living microbial community composition, especially Bacteria, Archaea, and Alphaproteobacteria. In Godthåbsfjord, changes in water temperature and meltwater intrusions are also expected to alter the zooplankton community compositions (Tang et al, 2011b;Møller et al, 2012), which could lead to the emergence of different zooplankton-associated bacterial communities. We suggest that climate change research in Greenland and other Arctic regions take into consideration the potential changes and responses of these microbial islands.…”
Section: Microbial Islands In a Changing Oceanmentioning
confidence: 99%
“…The study showed that this population had a strong transcriptomic response to an increase in temperature (from 0°C to 15°C) involving up-regulation of genes related to protein folding, transcription, translation and metabolism, and suggested 5°C as an optimum temperature. Physiological experiments on C. finmarchicus from the same area support this suggestion (Hjorth and Nielsen, 2011;Kjellerup et al, 2012), while studies from warmer areas suggest 10-12°C as an optimal temperature for C. finmarchicus (Harris et al, 2000;Møller et al, 2012). Given these observations and the fact that the distribution of C. finmarchicus is characterised by geographically varying ranges of temperature, salinity and light conditions (Melle et al, 2014), it is likely that response to environmental factors in C. finmarchicus is population-specific.…”
Section: Introductionmentioning
confidence: 58%